Discovery of indazole ethers as novel, potent, non-steroidal glucocorticoid receptor modulators. Issue 23 (1st December 2016) - Hemmerling, Martin; Edman, Karl; Lepistö, Matti; Eriksson, Anders; Ivanova, Svetlana; Dahmén, Jan; Rehwinkel, Hartmut; Berger, Markus; Hendrickx, Ramon; Dearman, Matthew; Jensen, Tina Jellesmark; Wissler, Lisa; et al.
Graphical abstract: Abstract: A structure-based design approach led to the identification of a novel class of indazole ether based, non-steroidal glucocorticoid receptor (GR) modulators. Several examples were identified that displayed cell potency in the picomolar range, inhibiting LPS-induced TNF-α release by primary peripheral blood mononuclear cells (PBMCs). Additionally, an improved steroid hormone receptor binding selectivity profile, compared to classical steroidal GR agonists, was demonstrated. The indazole ether core tolerated a broad range of substituents allowing for modulation of the physiochemical parameters. A small sub-set of indazole ethers, with pharmacokinetic properties suitable for oral administration, was investigated in a rat antigen-induced joint inflammation model and demonstrated excellent anti-inflammatory efficacy.